2014
DOI: 10.9790/3008-09275966
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of adherence Protein Hemagglutinin sub-unit Pili with MW 49.6 kDa Helicobacter pylori on Mice Gastric Epithelial Cell

Abstract: Helicobacter pylori (H.pylori) is a gram-negative microaerophilic bacterium that is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…In other bacteria, it was reported that a sub unit pili protein of Shigella dysentriae and Salmonella typhi with molecular weight of 49, 8 kDA and 48 kDa respectively were hemaglutinin with adhesion properties 15 . With H. pylori it selves, it has just recently published that a sub unit pili 49, 6 kDa protein of this microorganism was found to be immunogenic and immune dominant in vitro 11 . For this, we reasoned that this protein may be a potential candidate for protection against natural H. pylori infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other bacteria, it was reported that a sub unit pili protein of Shigella dysentriae and Salmonella typhi with molecular weight of 49, 8 kDA and 48 kDa respectively were hemaglutinin with adhesion properties 15 . With H. pylori it selves, it has just recently published that a sub unit pili 49, 6 kDa protein of this microorganism was found to be immunogenic and immune dominant in vitro 11 . For this, we reasoned that this protein may be a potential candidate for protection against natural H. pylori infections.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the in vivo biological properties of the sub unit pili 49,6 kDa protein of H. pylori were investigated. It was previously published that this protein could be purified for the in vitro studies which showed its immunogenicity 11 . In animal models, application of this protein mixed with a commercial cholera toxin adjuvant, revealed a significant inhibition against live H. pylori challenge in the mucosal gastric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic properties of these bacteria were associated with its fimbrial adhesion (pili) [11], a protein found on the bacterial cell surface that plays a role as a bacterial virulence factor [12]. In vitro studies using Western blotting analysis, hemagglutination test, adherence inhibition assays, and immunocytochemical staining revealed that the 49.6-kDa subunit pili protein of H. pylori was immunogenic [13]. The ability of this protein in agglutinating mouse erythrocytes indicates that it was hemagglutinin in nature [13].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies using Western blotting analysis, hemagglutination test, adherence inhibition assays, and immunocytochemical staining revealed that the 49.6-kDa subunit pili protein of H. pylori was immunogenic [13]. The ability of this protein in agglutinating mouse erythrocytes indicates that it was hemagglutinin in nature [13]. It was also confirmed that the protein possessed adhesion molecules that play a crucial role in the early phase of the pathogenesis when H. pylor i infiltrate into the epithelial cells of gastric [14-16].…”
Section: Introductionmentioning
confidence: 99%